The Role of NPY in the Regulation of Bone Metabolism - Chen, Qing-Chang; Zhang, Yan (Frontiers in Endocrinology, 2022)
Bone diseases are the leading causes of disability and severely compromise quality of life. Neuropeptide Y (NPY) is a multifunctional neuropeptide participate in various physiological and pathological processes and existed in both nerve system and bone tissue. In bone tissue, it actively participates in bone metabolism and disease progression through its receptors. Previous studies have focused on the opposite effects of NPY on bone formation and resorption through paracrine modes. In this review, we present a brief overview of progress made in this research field in recent times in order to provide a reference for further understanding the regulatory mechanism of bone physiology and pathological metabolism.